Turin and the British in the age of the Grand Tour - Bianchi, Paola 1964-; Wolfe, Karin (Cambridge University Press, 2017)
"The Duchy of Savoy first claimed royal status in the seventeenth century, but only in 1713 was Victor Amadeus II, Duke of Savoy (1666-1732), crowned King of Sicily. The events of the Peace of Utrecht (1713) sanctioned the decades-long project, the Duchy had pursued through the convoluted maze of political relationships between foreign powers. Of these, the British Kingdom was one of their most assiduous advocates, because of complimentary dynastic, political, cultural and commercial interests. A notable stream of British diplomats and visitors to the Savoy capital engaged in an extraordinary and reciprocal exchange with the Turinese during this fertile period. The flow of travellers, a number of whom were British emissaries and envoys posted to the court, coincided, in part, with the itineraries of the international Grand Tour which transformed the capital into a gateway to Italy, resulting in a conflagration of cultural cosmopolitanism in early modern Europe."--Back cover
Hier auch später erschienene unveränderte Nachdrucke
Aus dem Vorwort:"The conference Torino Britannica : Political and Cultural Crossroads in the Age of the Grand Tour (19-22 June 2013), co-organized by the British School at Rome and the Centro Studi della Reggia di Venaria, Turin"
Keywords: Geschichte 1700-1800; Geschichte 1680-1800; Geschichte 1600-1800; Geschichte; Kunst; Beziehung; Engländer; Diplomatische Beziehungen; Italien; Großbritannien; Turin; British / Italy / Turin / History / 18th century; Konferenzschrift -- British School at Rome -- 19.06.2013-22.06.2013 -- Rom; Konferenzschrift -- Centro Studi della Reggia di Venaria -- 19.06.2013-22.06.2013 -- Turin